Triplet Energy Transfer Mechanism of Ternary Organic Hybrid Thin Films of PFO/MEH-PPV/CsPbBr3 Perovskite Quantum Dots - Bandar Ali Al-Asbahi; Saif M. H. Qaid; Hamid M. Ghaithan; Abdullah S. Aldwayyan (Nanomaterials, 2020)
The triplet energy transfer mechanism of novel poly(9,9-di-n-octylflourenyl-2,7-diyl) (PFO)/poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV)/CsPbBr3 perovskite quantum dot (PQD) hybrid thin films was comprehensively investigated. The concentrations of PFO and MEH-PPV in all the specimens were fixed, while the PQD content was varied with various weight ratios and premixed by a solution blending method before it was spin-coated onto glass substrates. The triplet non-radiative Förster resonance energy transfers (FRETs) in the PFO/MEH-PPV/PQDs ternary blend, the dual FRET from PFO to both PQDs and MEH-PPV, and the secondary FRET from PQDs to MEH-PPV were observed. The values of the Förster radius (Ro) of FRET from PFO to MEH-PPV in the presence of various PQD contents (Case I) increased from 92.3 to 104.7 Å, and they decreased gradually from 68.0 to 39.5 Å for FRET from PFO to PQDs in the presence of MEH-PPV (Case II). These Ro values in both cases confirmed the dominance of FRET in ternary hybrid thin films. Upon increasing the PQD content, the distance between the donor and acceptor molecules (RDA) and the conjugation length (Aπ) in both cases gradually decreased. The small values of Ro, RDA, and Aπ with a decrease in the energy transfer lifetime (τET) due to an increase in the PQD contents in both Cases I and II confirmed the efficient FRET in the hybrid. To prevent intermolecular transfer in PFO, the concentrations of MEH-PPV (Case I) and PQDs (Case II) should be decreased to a range of 0.57–0.39 mM and increased in the range of 1.42–7.25 mM.